The Barriers Perceived by Chilean Athletes with Disability at Different Social Ecological Levels - De Moraes-Ferrari, G (Nature Research, 2025)
People with disabilities face various barriers that hinder or prevent access to physical activity, impacting their quality of health and life. This study aimed to examine the barriers to physical activity experienced by Chilean athletes with disability. The sample consisted of 35 Chilean athletes with disability. The participants answered the Physical Activity Questionnaire for People with Mobility Impairments (BPAQ-MI) to assess perceptions of social ecological subdivided into four levels. Sex, the type of sport practice, the region where live, the type of disability, and the physical disability were considered. The organizational level was the main barrier according to the ecological level, with the lack of adaptation of outdoor spaces and the lack of information or inclusive advertising in the sports center being the main barriers identified. An effect of the type of disability on the social ecological barriers was observed, with differences between the non-wheelchair user and wheelchair user groups. The organizational and community context were the main perceived barriers. Thus, it is considered relevant to generate actions for specific interventions in order to promote the practice of physical activity and reduce the main barriers identified in the different contexts within the community. © The Author(s) 2025.
Keywords: Social barriers; Social participation; Physical disability; Adapted sports